Gender and race matter global perspectives on being a woman. - Takhar, Shaminder; Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Bingley, U.K. : Emerald, 2016)
The drive for gender equality is not a recent phenomenon with the UN cited as occupying a central role for legislative change globally. Gender inequality persists in most countries and although it appears that we have a long way to go, this collection contributes to a feminist scholarship that highlights a destabilising of established patterns of behaviour and gender relations. It acknowledges the multiplicity of discrimination but locates women at the centre of a dialogue and presents key interventions in gender and race matters. For the contributors, gender serves as an analytical framework and covers the experiences of women in different global settings related to education, political activism, corporeal violence, identity, sexuality, and poverty. The use of poetry and literature provides a powerful voice for women against exclusion and recognises their contribution to society. This collection is innovative in not only relating experiential evidence but also putting forward how women are able to challenge oppression through circumventing rules, roles, obligations and prejudice through a powerful agency.
A century of Egyptian women's demands: the four waves of the Egyptian feminist movement / Hala Kamal -- The women's movement and neo-liberalism in Iran: between accommodation and resistance / Tara Povey -- Bangladeshi female students in higher education: agentic autonomy at the race/gender trajectory / Shaminder Takhar -- Women's education and employment in Iran / Elaheh Rostami-Povey -- Gender and caste intersectionality in India: an analysis of the Nirbhaya case December 16th 2012 / Adrija Dey, Bev Orton -- Negotiating gender security: the transnationalisation of local activist discourses in post-conflict Burundi and Liberia / Maria Martin de Almagro -- Gender security/sexuality in South Africa: I am HIV-positive. How could you do this to me? (Orford, 2006: 72) / Bev Orton -- Agency, resistance and subversion: voices in the field / Jaya Gajparia -- Re-mapping women's testimonies into networked subjectivities: the Quipu Project / Donatella Maraschin, Suzanne Scafe -- The body contours of Carnival: mas-playing and race in Trinidad / Kavyta Raghunandan -- Gender in post-liberalisation India: the complex trajectories of gender and (postcolonial) nationalism in Hindi cinema / Priyasha Kaul -- Migration, African writing and the post-colonial/diasporic Chimamanda Adichie moment / Carole Boyce Davies -- SUHA / Jocelyn Watson -- Woman with golden apple (no ordinary fruit) after Lotte Kramer's Boy With Orange (out of Kosovo) / Dorothea Smartt.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Gender Studies; Gender studies: women; Women's studies